دور التكنولوجيا الحديثة في تحول الاقتصادات الحديثة (Comprehensive Journal of Science, 2025)
This research aims to examine the role of modern technology in transforming modern economies byanalyzing its impact on digital infrastructure, human capital, innovation, economic performance, andsustainability. The study adopted a descriptive-analytical methodology supported by a field survey of 30participants from various institutions. The results indicate that institutions with advanced digitalinfrastructure achieve higher productivity, lower operational costs, and improved competitiveness. However,the study also reveals persistent challenges, such as the digital skills gap and limited technologicalinnovation, which hinder effective transformation. The study recommends adopting national digitaltransformation strategies, increasing investment in human capital development, and supporting researchand technological innovation to achieve sustainable economic growth.
Keywords: Modern Technology; Digital Transformation; Innovation; Digital Skills; Economic Sustainability